Study of stress-strain state of passenger car body (Transport systems and technologies, 2025)
The article presents the stress-strain state analysis results of the load-bearing elements of the body and frame of the 61-779 model passenger car. To assess the strength of the car body, the finite element method was used with the ANSYS software package. In the model, the body is represented as a system consisting of beam, shell, and solid finite elements. The connections are modeled using rigid links. The model contains a total of 890,436 nodes and 321,874 finite elements. Boundary conditions include restrictions of freedom in support nodes (fixed support) and applied external loads. The main load-bearing element of the car structure is the center sill, made of I-beam profile No. 30. Additional fastening elements are used to increase the stiffness of the connections between the center sill and the crossbeams. The sheathing is made of structural and stainless sheet steel. Corrugated metal 2 mm thick is used as the outer sheathing. A study was conducted on the stress-strain state of the car body with nominal dimensions. The highest stress under load occurs in the bolster beam at the point of contact with the end beam of the frame and amounts to 258 MPa. The stress in the body sheathing between window openings is 65 MPa. The results obtained will further determine the direction of research on the optimization of load-bearing structures of the frame and body.
Keywords: railway transport; passenger car; body; reliability; load; wear; stresses; optimization